Comparison of NDWI, MNDWI1 and MNDWI2 Indices from Sentinel-2 Satellite Images for Extracting Urban Surface Water Bodies in Khon Kaen - Sawetwong, Chaiyarit; Reungsang, Pipat (Journal of Applied Informatics and Technology, 2021)
The objective of this research is to compare methods for determining the Normalized Difference Water Index (NDWI) and the Modified Normalized Difference Water Index (MNDWI) and resistance to urban and urban disturbances. From classification of visual information (Pixel-based) to extract surface water areas from Sentinel-2 satellite imagery. By checking for accuracy with the surface water area dragged the boundary from satellite imagery data from Google Earth found that the ideal Threshold of the NDWI Index is 0.1 and that of the MNDWI index is 0.35. Which is overall accurate at both 0.58, the MNDWI index was more efficient than the NDWI index.